Cell cycle associated protein 1 associates with immune infiltration and ferroptosis in gastrointestinal cancer - Yan Gao; Ruimin Wu; Zhijun Pei; Changbin Ke; Daobing Zeng; Xiaohui Li; Yanmin Zhang (Heliyon, 2024)
Background: Cell Cycle-Associated Protein 1 (CAPRIN1) play an important role in cell proliferation, oxidative stress, and inflammatory response. Nonetheless, its role in tumor immunity and ferroptosis is largely unknown in gastrointestinal cancer patients. Methods: Through comprehensive bioinformatics, we investigate CAPRIN1 expression patterns and its role in diagnosis, functional signaling pathways, tumor immune infiltration and ferroptosis of different gastrointestinal cancer subtypes. Besides, immunohistochemistry (IHC) and immune blot were used to validate our esophagus cancer clinical data. The ferroptotic features of CAPRIN1 in vitro were assessed through knockdown assays in esophagus cancer cells. Results: CAPRIN1 expression was significantly upregulated, correlated with poor prognosis, and served as an independent risk factor for most gastrointestinal cancer. Moreover, CAPRIN1 overexpression positively correlated with gene markers of most infiltrating immune cells, and immune checkpoints. CAPRIN1 knockdown significantly decreased the protein level of major histocompatibility complex class I molecules. We also identified a link between CAPRIN1 and ferroptosis-related genes in gastrointestinal cancer. Knockdown of CAPRIN1 significantly increased the production of lipid reactive oxygen species and malondialdehyde. Inhibition of CAPRIN1 expression promoted ferroptotic cell death induced by RAS-selective lethal 3 and erastin in human esophagus cancer cells. Conclusion: Collectively, our results demonstrate that CAPRIN1 is aberrantly expressed in gastrointestinal cancer, is associated with poor prognosis, and could potentially influence immune infiltration and ferroptosis.